PENGARUH EXPERIENTIAL MARKETING & KUALITAS ACARA TERHADAP MINAT BERKUNJUNG ULANG MELALUI KEPUASAN PENGUNJUNG SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PENGUNJUNG ACARA MINGGUAN HUMA BETANG NIGHT PALANGKA RAYA) - Sihombing, Salbetta; Kristinae, Vivy; Borneo Poetra, Gema; Meitiana, Meitiana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the effects of experiential marketing and event quality on revisit intention, mediated by visitor satisfaction, in the weekly Huma Betang Night cultural event (Palangka Raya, Indonesia). A quantitative survey of 75 visitors was analyzed using PLS-SEM (SmartPLS 3.0). Results indicate positive, significant paths: experiential marketing → satisfaction (β = 0.392; p < 0.001), event quality → satisfaction (β = 0.404; p < 0.001), satisfaction → revisit intention (β = 0.431; p < 0.001), experiential marketing → revisit intention (β = 0.251; p = 0.002), and event quality → revisit intention (β = 0.262; p = 0.005). Satisfaction partially mediates the effects of experiential marketing (indirect β = 0.169; p = 0.001) and event quality (indirect β = 0.174; p < 0.001) on revisit intention. Model explanatory power is moderate (R² satisfaction = 0.321; R² revisit intention = 0.497). The findings highlight the importance of sensory–affective experiences and service/process quality to strengthen visitor satisfaction and revisit intention in secondary-city cultural night contexts.